Prosperity deferred: conservationism and conflicts over development in Dukuduku, Kwazulu Natal, 1980 to the present - Nyathi, Patrick (My University, 2021)
The research project explores the debates revolving around nature conservation in a unique indigenous forest of Dukuduku, Mtubatuba, in the northern KwaZulu Natal coastal belt between 1980 and the present. Dukuduku area is situated close to and borders the Greater St Lucia Wetland Park (GSLWP), which is a renowned international tourist attraction and the tourism hub of South Africa in general and KwaZulu Natal in particular. The history of this part of the province is characterised by forced displacement of African people who had occupied this area before it was incorporated into the British Natal province. Once annexed by British the area was demarcated as a state land, which marked the commencement of forced displacement in September 1930. Such forced removals led to violent confrontation as the forest dwellers confronted authorities in a fight against unjust displacement. As a result, the study sought to investigate and trace the extent of forced removals in Dukuduku forest, examining the livelihoods of the African families in occupation of the forest over time. Displacement in Dukuduku forest was driven by the potential profit the area would provide the colonial government. Initially displacement was meant to pave way for agricultural activities such as commercial forestry and sugarcane production which commenced in 1911. In addition, Dukuduku presents a good example of a remote traditional area, which the government claim is a state land but there has been the co-existence of the traditional leadership institution and local democratic structures. This, is believed to have been the cause of conflict between these two leadership institutions at a local level. Land claimants have come into play in the recent past exacerbating conflicts over land administration and social development in the area. The study was conducted in the Dukuduku Area (Dukuduku Forest, Ezwenelisha and Khula village), Mtubatuba in the northern KwaZulu Natal province and seeks to explore conflicts revolving around conservationism and address the question of land ownership and land administration in the area
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021